ANALISIS YURIDIS PERSEROAN PERORANGAN DITINJAU DARI UNDANG-UNDANG CIPTA KERJA DAN UNDANG-UNDANG PERSEROAN TERBATAS - Sylvia Putri; David Tan (UNES Law Review, 2022)
The current crisis situation, due to the Covid-19 pandemic, has caused the government to enact the Job Creation Law as an effort to advance the economy, in particular, micro and small businesses. The existence of the Job Creation Law expands the concept of a limited liability company with the recognition of a new legal entity, namely an individual company. The existence of an individual company gave birth to a number of contradictions in the basic concept of a limited liability company. This normative juridical research will discuss the regulation of micro and small business criteria based on the Job Creation Law and the limited liability company law as well as legal loopholes and proposed improvements. This study aims to determine the arrangements related to individual companies. The results of the study indicate that the legal basis for individual companies still has legal loopholes so that the government plays an important role in strengthening the regulation.